Feasibility of afforestation as an equitable nature-based solution in urban areas. (June 2022) - Chakraborty, T.; Biswas, T.; Campbell, L.S.; Franklin, B.; Parker, S.S.; Tukman, M.
HIghlights: Tree cover and urban heat island disparities examined for cities in California. Available area for afforestation computed for urban census block groups (CBGs). Benefits of urban afforestation to reduce land surface temperature quantified. Ancillary data combined to compute multiple co-benefits of urban afforestation. CBGs scored to prioritize equitable afforestation using new suitability algorithm. Abstract: Although nature-based solutions for urban heat mitigation have gained momentum, it is important to quantitatively assess the feasibility of such strategies to utilize space efficiently and prioritize lower-income communities, who have fewer options for climate change adaptation. Here we combine data from US census estimates, satellites, and satellite-derived products to develop a framework to target potentially suitable areas for urban afforestation to mitigate urban heat and minimize tree cover disparity. We test this framework for California and show that space exists for an additional 36 million (1.28 million acres of) trees in the state's urban areas. This would reduce the average urban land surface temperature by 1.8°C and provide multiple co-benefits totaling $1.1 billion annually, including reduction in heat-related medical visits (almost 4000 over 10 years) and 4.5 million metric tons of annual CO2 sequestration. Because funding is limited, we provide suitability scores for urban afforestation at the census block group (CBG) scale based on multiple considerations. In California, afforestation in CBGs with positive suitability scores will lead to $712 million of net annual benefits (against an annual investment of $467 million) and will serve 89% of the ≈9 million urban residents in the lowest income quartile for their cities. This method can guide equitable urban afforestation efforts and be scaled to other North American cities.